O Optimalisasi: Optimalisasi Toga dan Dasa Wisma (Dawis) sebagai Sumber Gizi bagi Masyarakat dalam Rangka Pencegahan Stunting di Desa Sungai Paku Kecamatan Kampar Kiri - Fifia Chandra; Monalisa Siagian; Chindy Marza Lena Aditya; Ajeng Setyawati; Fadilla Fadilla; Fahrezi Dinl Alfikri; Ikka Salamah; Junaidi Junaidi; Najmi Hilalyati Absi; Teopils Barus; Viola Ultrimahreza (Educativo: Jurnal Pendidikan, 2023)
Abstract Optimization of Family Medicinal Plants (Toga) and Dasa Wisma (Dawis) as a Source of Nutrition for the Community in the Context of Stunting Prevention in Sungai Paku Village, Kampar Kiri District. The target of this service activity regarding the use of Toga and Dawis in efforts to strengthen family food and prevent stunting is Mrs. -Adab PKK mothers in Sungai Paku Village, Kampar Kiri District with the number of participants consisting of 4 different hamlets. In this activity, resource persons were used by students from the University of Riau, Faculty of Agriculture, Faculty of Fisheries, Faculty of Teacher Training and Education and Government Sciences who were guided by Field Supervisors from the Faculty of Medicine, University of Riau. Based on the results obtained, the use of the Toga and Dawis yards was not optimal. This can be seen in the grassy toga and Dawsi plants, there are areas of Pekaranga that are still empty without plants. Through this community empowerment program, the community is expected to be able to manage and utilize existing yards. In utilizing Toga and Dawis' yard land, conceptually the benefits of Toga and Dawis can be taken into account which are productive: a) Many people are not aware of the results of Toga and Dawis which can provide additional income such as medicines or food for daily living needs. -day. -days in order to live easily, cheaply and healthily. b) Toga and Dawis land use is part of creating a comfortable, healthy and beautiful environment that is sustainable and environmentally friendly (sustainable development). c) improve the quality of a cool, healthy and beautiful environment. d) can spread family creativity e) provide comfort and the physical and spiritual needs of the family f) utilize the yard with educational value. Based on data obtained from Posyandu activities in Sungai Paku Village, it was recorded that in July 2023 there was 1 child under five who was affected by stunting. From this data, it was found that Sungai Paku Village is one of the villages with a low level of stunting disease and is considered to have recovered. However, to break the chain of stunting in children, continuous efforts are certainly needed and must always be paid attention to by the community and the government. One of the factors of stunting is nutritional adequacy. Even though there have been improvements, there is a possibility that stunting could occur again in the community. Keywords : optimalization of Toga and Dawis plants